Under surge, under siege : the odyssey of Bay St. Louis and Katrina - Anderson, Ellis (University Press of Mississippi, 2010)
"Hurricane Katrina tore into Bay St. Louis, Mississippi, raking away lives, buildings, and livelihoods in a place known for its picturesque, coastal views; its laid-back, artsy downtown; and its deep-dyed southern cordiality. The tragedy also revealed the inner workings of a community with an indomitable heart and profound neighborly bonds. Those connections often brought out the best in people under the worst of circumstances. In Under Surge, Under Siege, Ellis Anderson, who rode out the storm in her Bay St. Louis home and sheltered many neighbors afterwards, offers stories of generosity, heroism, and laughter in the midst of terror and desperate uncertainty"--Page 2 of cover